The Influence of Chemical Weapons on Tactics and Operational Art in World War 1 (Essays in the History of Chemical Weapons), Part 3 - M. V. Supotnitskiy; S. V. Petrov; V. A. Kovtun (Вестник войск РХБ защиты)
The introduction of poison gases by the Germans at Ypres in April 1915 marked a new era in modern warfare. The cylinder attack of the German Army against the French and the British positions at Ypres on April 22, 1915, became the first large-scale appearance of the new kind of weapons, chemical weapons, on the battlefields of World War 1. The widespread use of chemical munitions of different types, numerous toxic agents and their delivery systems (field and heavy artillery, mortars and Livens projectors) by all the belligerents influenced military tactics and operational art at World War 1. In 1915-1916, during the period of trench warfare, the use of chemical weapons for breaking through the enemy`s first defence lines changed the structure of combat orders and led to their dispersal and the deployment in depth of the defensive zone. In 1917 chemical weapons made it possible to overcome the contradiction between the lengthy preliminary artillery bombardment and the surprise of the offensive. The unprecedented artillery chemical bombardments fired by the German Army, artillery chemical battle, resulted in the significant success of the Germans in spring offensives in 1918, when large parts of the front were given up by the retiring Allied forces. The dynamics of the growth of the chemical warfare agents` (CWA) production, the development of means and methods for delivering the agents efficiently to the target by the Allied countries allowed the authors to suggest that in case Germany had not signed the armistice of 11 November 1918 with the Allies, the large-scale battlefield use of chemical weapons could multiply both in quality and in quantity. The development of the bombardment aviation and the inability of Germany to carry out a retaliatory chemical attack, that became obvious at the end of 1918, offered a golden opportunity for the Allies to use chemical agents in 1919 without any legal or humanitarian limitation on the methods of warfare. This article is concerned also with tactical and operational objectives and targets the belligerents tried to achieve by using chemical weapons during separate battles, the evolution of chemical weapons and chemical warfare agents and their joint impact on military operations at the battlefields of World War 1.